PERANCANGAN SISTEM MANAJEMEN STOK BARANG BERBASIS WEB PADA PT.X - Visant Tristan Gumilang (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Goods stock management is a policy or decision of a company that has the goal of determining the company can provide quality inventory of goods such as managing the amount of goods. Basically, stock management is a process in a warehouse where stock availability is influenced by external factors such as orders from buyers and internal factors such as supply of goods. Every company certainly has a stock of goods for sales. If a company has a lot of stock, of course it needs a stock management system that can be accessed anywhere or web-based. By managing web-based inventory management, users can manage inventory on any platform. One of the keys for a company to have an orderly stock of goods is to use a stock management system. The purpose of designing this system is to form a stock management system and maintenance of a company's data. After already having an application system, it will be easier for the user to find out the details of the stock of goods and information related to the goods of companies that are carrying out maintenance and the process of monitoring stock of goods. The data used in the design of this system is detailed stock data for ink companies located in Jakarta. The data used is the company's inventory data for 2020 january to december. The method used is the SDLC waterfall method. In designing the application system, two stages of design are carried out, namely process design and database design. The tests were carried out using the blackbox testing method and focused beta testing through questionnaires to users at PT.X. After testing, suggestions have been given. Applications that have been made should be given a language change feature because currently the application is still in english, so that some employees who cannot speak english will have difficulty understanding this application.